Strategy formation development approaches of the regional scientific and educational cluster in the context of spatial development of territories - N. V. Andreeva; A. V. Gerasimov (Управление)
To ensure sustainable socio-economic development of the regions, it is necessary to select the main priorities when forming a strategy for the development and successful functioning of economic systems. In this regard, it  is important to search for new sources of innovative development, which can be achieved by forming various forms of cluster integration at the level of the Federation subjects, ensuring interaction between educational institutions, business structures, as well as state structures engaged in research and development activities located on the same territory. For effective functioning of the cluster, it is necessary to form a mutual interest of all interested participants. This makes it possible to effectively use organizational opportunities for the  development of territories and form a strategy for their development.The article considers approaches to developing a strategy for the formation of a regional scientific and  educational cluster as a new form of spatial organization of the economy at the regional level, which consists in  taking into account the strategic directions of development of the region and its territories based on the principles of system and process interaction. The role of cluster integration of science and education institutions in solving strategic tasks of socio-economic development of regions has been shown. The relationship between the strategic direction of development of regional scientific and educational cluster structures and the priorities of regional strategic development has been clarified and revealed. The sequence of formation of the strategy of the regional scientific and educational cluster, including analytical, functional-content and evaluation stages, has been established. The University complex, which is the “core” of creating a scientific and educational cluster in a regional economy, can be considered as the most promising form of optimizing the activities and development of higher educational institution. In this regard, this task becomes particularly relevant in the implementation of the concept of integration of the triad of production (business), science and education. The main elements of  the management system for the strategic development of a regional scientific and educational cluster  containing components of a content and tool subsystem have been proposed.